2005
DOI: 10.1093/rheumatology/kei084
|View full text |Cite
|
Sign up to set email alerts
|

Association of radiological hand osteoarthritis with bone mineral mass: a population study

Abstract: Our results indicate a direct relation of both radiological DIP osteoarthritis and CMC-1 osteoarthritis with low cortical bone mineral mass, in proportion to the severity of osteoarthritis. The presence of symmetrical DIP osteoarthritis, a possible indicator of generalized osteoarthritis, suggests an increased risk of osteoporosis over time.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
0
2

Year Published

2009
2009
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(30 citation statements)
references
References 33 publications
1
27
0
2
Order By: Relevance
“…In the same vein, authors observed that erosive arthrosis in the hands was associated with lower T and Z-score indices in the lumbar spine than in controls 27 . Lastly, Haara et al 28 confirmed that the loss of bone mass over 20 years, evaluated by means of quantitative ultrasound in the calcaneum, was more pronounced in those patients with arthrosis of the interphalangial joints.…”
Section: Peripheral Arthrosis and Osteoporosismentioning
confidence: 90%
See 1 more Smart Citation
“…In the same vein, authors observed that erosive arthrosis in the hands was associated with lower T and Z-score indices in the lumbar spine than in controls 27 . Lastly, Haara et al 28 confirmed that the loss of bone mass over 20 years, evaluated by means of quantitative ultrasound in the calcaneum, was more pronounced in those patients with arthrosis of the interphalangial joints.…”
Section: Peripheral Arthrosis and Osteoporosismentioning
confidence: 90%
“…However, the analysis of the possible relationship between the two processes is problematic due to various factors, some of which have been suggested in different studies 17,28,35,53,54 . Firstly, it is possible that there are different patterns of association as a function of the location of the arthrosis.…”
Section: Discussionmentioning
confidence: 99%
“…Some findings from cross-sectional [2] and longitudinal [3,4] studies have shown the coexistence of osteoarthritis and osteoporosis or even an unexpected increased risk of vertebral fractures in patients with spondyloarthritis [5,6]. In this last scenario, however, few radiology-based studies have been reported [5][6][7][8][9][10][11]; most of these have included postmenopausal women and have analyzed only the lumbar spine, with a paucity of data on the thoracic spine.…”
Section: Introductionmentioning
confidence: 99%
“…Bazı çalışmalarda (8,12) el OA ile OP arasında herhangi bir ilişki gösterilemezken, bazı çalışmalarda (15,16) el OA olan hastalarda kontrol grubuyla kıyasla omurgada ve femurda düşük KMY olduğu bildirilmiştir. Ayrıca, literatürde özellikle radyogra k olarak el OA olan hastalarda periferik kemiklerde de OP riskinin artmış olduğunu öne süren çalışmalar mevcuttur (17)(18)(19). Bu çalışmanın birincil amacı el OA olan postmenopozal kadınların KMY değerlerini el OA olmayan bireylerle karşılaştırmaktır.…”
Section: Introductionunclassified